Design of lateral heterostructure from arsenene and antimonene. (8th September 2016) - Sun, Qilong; Dai, Ying; Ma, Yandong; Yin, Na; Wei, Wei; Yu, Lin; Huang, Baibiao
Abstract: Lateral heterostructures fabricated by two-dimensional building blocks have opened up exciting realms in material science and device physics. Identifying suitable materials for creating such heterostructures is urgently needed for the next-generation devices. Here, we demonstrate a novel type of seamless lateral heterostructures with excellent stabilities formed within pristine arsenene and antimonene. We find that these heterostructures could possess direct and reduced energy gaps without any modulations. Moreover, the highly coveted type-II alignment and the high carrier mobility are also identified, marking the enhanced quantum efficiency. The tensile strain can result in efficient bandgap engineering. Besides, the proposed critical condition for favored direct energy gaps would have a guiding significance on the subsequent works. Generally, our predictions not only introduce new vitality into lateral heterostructures, enriching available candidate materials in this field, but also highlight the potential of these lateral heterostructures as appealing materials for future devices.